Should Instructors Require Discussion in Online Courses? Effects of Online Discussion on Community of Inquiry, Learner Time, Satisfaction, and Achievement - Cho, Moon-Heum; Tobias, Scott (International Review of Research in Open and Distributed Learning, 2016)
Online discussion is a commonly used means to promote student understanding of a topic and to facilitate social interaction among students or between students and instructor; however, its effects on student learning in online learning environments have rarely been investigated. The purpose of this study was to examine the role of online discussion in student learning experiences measured with community of inquiry, learner time, satisfaction, and achievement. One instructor taught the same online course for three consecutive semesters using three different conditions. During one semester enrolled students engaged in no discussion, during another semester they engaged in discussion without instructor participation, and in the remaining semester they engaged in discussion with active instructor participation. No significant differences were found among conditions in cognitive presence and the instructor’s teaching presence, whereas significant difference was found in social presence among conditions. No significant differences among conditions were found time spent on Blackboard, course satisfaction, and student achievement. Implications for online teaching and learning as well as for designing an online course conclude the paper.